Physiological Plausibility Can Increase Reproducibility in Cognitive Neuroscience. Issue 8 (August 2016) - van Ede, Freek; Maris, Eric
Abstract : Physiological measurements offer the unique opportunity to assess plausibility along multiple data dimensions, in addition to the significance of statistical tests. Increased emphasis hereon should help increase the reproducibility of research findings by turning what is often considered a threat to reproducibility (a large search space) into part of the solution.